FPGA based new MPPT (maximum power point tracking) method for PV (photovoltaic) array system operating partially shaded conditions - Parlak, Koray Sener (Pergamon-Elsevier Science Ltd, 2014)
In PV (photovoltaic) systems, MPPT (maximum power point tracking) methods play highly crucial role for its own research domain. Researchers can get effective results using traditional MPPT methods which work well under uniform irradiance conditions. On the other hand mentioned methods cannot always run successfully since there is more than one local maxima in PV characteristics under partial shading conditions. Under partial shading conditions, one can meet to various approaches in the literature working accurately they can, however, reveal complex calculations or requires some of extra parameters such as datasheet values, system configuration data. Here, we propose a novel MPPT method providing GMPP (global maximum power point) for PV arrays under any environmental conditions. This method is based on sensing the current and voltage values of a capacitor connected to the output of the PV array during the charging time. Then it compares instantaneous power values to maximum power, and estimates maximum power value and corresponding voltage value. Matlab-Simulink and FPGA based test system have been utilized for verification stage of the proposed MPPT method under uniform and partially shaded conditions, and we got promising results. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Photovoltaic panels; Partial shaded conditions; Maximum power point tracker; FPGA